Fungal Intelligence and the Posthuman: Mycohuman Art, Entangled Theory, and Fungi in (Eco-)Gothic Narratives - Gruss, Susanne (Journal of Posthumanism, 2024)
Fungi have become paradigmatic for the wonders, the adaptability, and the resilience of the nonhuman in publications, ranging from Anna Tsing Lowenhaupt’s anthropological analysis of the matsutake mushroom (2015) to Merlin Sheldrake’s popular take on the ‘world-making’ capacity of fungi (2020). This article explores different conceptualisations of ‘fungal intelligence’ and the posthuman in art, (popular) science, and literature. It argues that fungi are invested with a utopian potential in the first two. In literary texts, however, encounters of the human and the fungal worlds and the concomitant creation of a fungal posthuman veer towards the gothic. In a three-step argument, the article moves from the world of contemporary art to the recent flurry of textual production about fungi in anthropology and (popular) science and the construction of fungal intelligence in many of these texts.